Refugio tropical. Tensoestructuras en Costa Rica - Flor, Jan-Frederik (2015)
The paper reports on the experience of a student project where a tensile membrane structure was built as part of a academic activity. The historical origins as well as the modern development of membrane structures architecture at a global scale get introduced. In comparison the development of the membrane building technology in Costa Rica is traced and various recent examples are presented. By way of introduction to the description of the project the basic principles of tensile structures are presented including structure, materials, details and geometries. A detailed description of the processes of design, fabrication and installation is given as well as the analysis studies of sun and wind, which were used to adapt the design to tropical climate conditions.